Trauma, attachment, and family permanence : fear can stop you loving - Archer, Caroline, 1948-; Burnell, Alan (Jessica Kingsley Publishers, 2003)
Exploring the complex issues of trauma, attachment and family placement, the contributors to this book provide a variety of complementary perspectives on practice in this area. Focussing on how to integrate attachment theory and developmental psychology in practice with adopted or fostered children, they emphasise the need for understanding of early trauma and its effect on child development. Examining multiple aspects of work with children who are unable to live with their birth families, the book includes contributions on: new approaches to matching children with families; effective manageme.